A Study On The Small And Medium-Sized Enteprises' (Smes) Perception Towards Islamic Banking Products And Services: Implication On The Marketing Strategy In Competitive Environment - Amir Shaharuddin; Suhaila Abdul Hamid; Yasmin Hanani Mohd Safian (Universiti Sains Islam Malaysia, 2024)
Small and Medium Enterprises (SMEs) play an important supportive role in the Malaysian economy. In capturing this market segment, Islamic banks offer various banking products to cater SMEs' needs in daily business transactions. This research examines their perception towards the banking products offered which includes a study on their level of acceptance, knowledge, factors considered important in bank selection, current marketing strategy and customer satisfaction in Islamic banking. The research adopted a survey-based approach in collecting the data by distributing a set of selfadministered questionnaires to the potential SMEs. A total of 180 SMEs from Federal Tenitory of Kuala Lumpur, Selangor and Negeri Sembilan participated in this research. The results indicate that majority of the SMEs still do not consider the Islamic banks as the most desirable financial institution. The less effective marketing strategy has been identified as one of the reasons contributing to the low acceptance of products offered. It is also found that variances in the SMEs profiles infleunce their perception towards Islamic banking. The research concludes with some recommendations to be adopted in enhancing the effectiveness of Islamic banks marketing strategy.